Ureteral dilation recovery after intravesical reimplantation in children with primary obstructive megaureter - He, Yan; Wu, Xuemin; Xu, Yingrui; Liu, Zhaoquan; Du, Guoqiang; Wu, Xiangyu; Liu, Wei; Wu, Rongde (Frontiers in Pediatrics, 2023)
Abstract Background: To observe the postoperative recovery following ureteral dilation in primary obstructive megaureter (POM) after ureteral implantation, and evaluate the risk factors affecting ureter diameter resolution. Materials and Methods: A retrospective study was performed in patients with POM who underwent ureteral reimplantation using the Cohen procedure. Patient characteristics, perioperative parameters, and postoperative outcomes were also analysed. A widest ureteral diameter of < 7 mm was defined as a normal shape and outcome. Survival time was defined as the time from surgery to ureteral dilation recovery or to the last follow-up. Results: A total of 49 patients (54 ureters) were included in the analysis. The survival time ranged from 1 to 53 months. The shapes of a total of 47 (87.04%) megaureters recovered, and most (29/47) resolutions happened within 6 months after surgery. In the univariate analysis, bilateral ureterovesical reimplantation (p=0.015), ureteral terminal tapering (p=0.017), weight (p=0.036), and age (p=0.015) were associated with the recovery time of ureteral dilation. A delayed recovery of ureteral diameter was noted in bilateral reimplantation (HR=0.336, p=0.017) using multivariate Cox regression. Conclusions: Ureteral dilation in POM mostly returned to normal within six postoperative months. Moreover, bilateral ureterovesical reimplantation is a risk factor for delayed postoperative recovery of ureter dilation in POM.